TEACHING ENGLISH AS A FOREIGN LANGUAGE APPLYING SLANG AND METAPHORS IN THE PROCESS OF TEACHING (American Journal of Pedagogical and Educational Research, 2023)
The article focuses on teaching slang and metaphors, an integral part of any language, on the analysis of language learners’ beliefs and attitudes. The interpretations of “slang” and “metaphor” are given; the functions which they have in a language are examined and illustrated by examples representing the way they are used in speech by native speakers. The most common and effective techniques applied for teaching students slang and metaphors are analyzed.